Conceptual Design of a Universal Donor Screening Approach for Vaginal Microbiota Transplant - DeLong, Kevin; Bensouda, Sabrine; Zulfiqar, Fareeha; Zierden, Hannah C.; Hoang, Thuy M.; Abraham, Alison G.; Coleman, Jenell S.; Cone, Richard A.; Gravitt, Patti E.; Hendrix, Craig W.; Fuchs, Edward J.; Gaydos, Charlotte A.; et al. (Frontiers in Cellular and Infection Microbiology, 2019)
The success of fecal microbiota transplant (FMT) in treating recurrent Clostridioides difficile infection has led to growing excitement about the potential of using transplanted human material as a therapy for a wide range of diseases and conditions related to microbial dysbiosis. We anticipate that the next frontier of microbiota transplantation will be vaginal microbiota transplant (VMT). The composition of the vaginal microbiota has broad impact on sexual and reproductive health. The vaginal microbiota in the “optimal” state are one of the simplest communities, dominated by one of only a few species of Lactobacillus. Diversity in the microbiota and the concomitant depletion of lactobacilli, a condition referred to as bacterial vaginosis (BV), is associated with a wide range of deleterious effects, including increased risk of acquiring sexually transmitted infections and increased likelihood of having a preterm birth. However, we have very few treatment options available, and none of them curative or restorative, for “resetting” the vaginal microbiota to a more protective state. In order to test the hypothesis that VMT may be a more effective treatment option, we must first determine how to screen donors to find those with minimal risk of pathogen transmission and “optimal” vaginal microbiota for transplant. Here, we describe a universal donor screening approach that was implemented in a small pilot study of 20 women. We further characterized key physicochemical properties of donor cervicovaginal secretions (CVS) and the corresponding composition of the vaginal microbiota to delineate criteria for inclusion/exclusion. We anticipate that the framework described here will help accelerate clinical studies of VMT.